Analysis of The Influence of Behavior Intention, Technology Effort Expectancy and Digitalization Performance Expectancy on Behavior To Use of QRIS Users in Small Medium Enterprises Sector - Afan Suyanto, Mohamad; Candra Dewi, Luh Komang; Dharmawan, Donny; Suhardi, Dadang; Ekasari, Silvia (SEULANGA SYSTEM PUBLISHER, 2024)
The goal of this study is to see if performance and effort expectations influence behavior intention and, consequently, usage behavior. This study's target audience is QRIS users in micro, small, and medium-sized companies (MSMEs). We used 100 respondents as samples. Data was gathered using two methods: observation and interviews. To ensure that the data collected exhibited a strong association, we performed the validity test using the product moment correlation technique. Before beginning the path analysis test, the researcher used the provided framework to develop a structural equation. The interpretation results lead us to the following conclusions: The variable of performance expectancy has a direct effect on behavior intention. The variable effort expectancy has a direct effect on behavior intention. The variable's performance and effort expectations have a direct impact on behavior intention. The changing performance expectancy has a direct impact on user behavior. The variable effort expectancy has a direct impact on user behavior. The variable behavior intention has a direct impact on user behavior. The variables behavior intention, performance expectancy, and effort expectancy all have a direct impact on user behavior. The performance expectancy variable influences user behavior indirectly through behavior intention. The effort expectancy variable influences user behavior indirectly through behavior intention.